18S: A comprehensive dataset on spatiotemporal variation of microbial plankton communities in the Baltic Sea - Meike Latz; Agneta Andersson; Sonie Brugel; Mikael Hedblom; Krzysztof Jurdzinski; Bengt Karlson; Markus Lindh; Jenny Lycken; Anders Andersson (Royal Institute of Technology, 2023)
A dataset covering spatiotemporal variation in eukaryotic microbial communities and physicochemical parameters of the Baltic Sea. Between January 2019 and February 2020, 281 transect-time course samples and 65 samples for protocol testing were collected from 19 stations in the Baltic Sea, Kattegat and Skagerrak. We analysed the samples with 18S ribosomal RNA (rRNA) gene and 16S rRNA gene metabarcoding, to capture the eukaryotic and prokaryotic diversity, respectively.

Note that this resource was previously published as 'Metadata-only'.

This dataset was published via the SBDI ASV portal (https://asv-portal.biodiversitydata.se/).
Keywords: prokaryotic plankton; 16S rRNA metabarcoding; 18S rRNA metabarcoding; salinity; brackish water; marine monitoring; temporal variation; Observation; microbial plankton; eukaryotic plankton; Occurrence; Baltic Sea; Observation; OCCURRENCE; Biological Sciences; Biologi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Microbiology; Mikrobiologi